2022
DOI: 10.3389/fmolb.2022.821137
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Small Non-coding RNAs by Severe Acute Respiratory Syndrome Coronavirus 2 Infection

Abstract: The ongoing pandemic of coronavirus disease 2019 (COVID-19), which results from the rapid spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a significant global public health threat, with molecular mechanisms underlying its pathogenesis largely unknown. In the context of viral infections, small non-coding RNAs (sncRNAs) are known to play important roles in regulating the host responses, viral replication, and host-virus interaction. Compared with other subfamilies of sncRNAs, inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…The 5 -tDRs 5008c, 5013c, 5027c and 5028c were decreased in COVID-19 patients, and 5020a was increased. As previously reported, the 5 tDRs, were significantly changed in response to SARS-CoV-2 infection [17]. In addition, an assessment of patients above 60 years old that were diagnosed with COVID-19 compared to patients below 60 years old with COVID-19 revealed that 5013c was increased and 5019a was decreased (File S1).…”
Section: Tdr Expression Is Altered In Sars-cov-2 Infected Patients' P...supporting
confidence: 73%
See 2 more Smart Citations
“…The 5 -tDRs 5008c, 5013c, 5027c and 5028c were decreased in COVID-19 patients, and 5020a was increased. As previously reported, the 5 tDRs, were significantly changed in response to SARS-CoV-2 infection [17]. In addition, an assessment of patients above 60 years old that were diagnosed with COVID-19 compared to patients below 60 years old with COVID-19 revealed that 5013c was increased and 5019a was decreased (File S1).…”
Section: Tdr Expression Is Altered In Sars-cov-2 Infected Patients' P...supporting
confidence: 73%
“…Viruses are also known to produce sncRNAs from their own genomes [16]. Viral encoded small RNAs have recently been identified in SARS-CoV-2-infected cells [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an additional illustration of the utility of tatDB, we provide here an example of a possible hypothesis generation for interpreting of the results of the current active research in coronavirus. We have noted earlier various factors linking the features of the SARS-CoV-2 genome with short RNAs ( 45 ), and were also intrigued by an observation of a significant increase in tRF levels in patient samples ( 46 ). Although the tRF IDs in that paper do not match ours, we performed a sequence search of a highly upregulated (∼35 fold) tRF5-Leu-AAG in tatDB and identified RPL18A as a potential target.…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding RNAs (ncRNAs) comprise most of the human genome (as compared with protein-coding RNAs) [ 4 , 5 ], and their functions in physiological and pathological settings are increasingly recognized. tRNA-derived RNA fragments (tRFs) are a recently discovered category of ncRNAs whose importance in viral infectious diseases is becoming more evident [ 6 , 7 , 8 , 9 , 10 ]. We have recently shown that RSV infection induces a significant increase in tRFs.…”
Section: Introductionmentioning
confidence: 99%